Microbubble-Induced Phospholipase C Activation Does not Correlate with Platelet Aggregation - Malmgren, R; Thorsen, T; Nordvik, A; Holmsen, H (Thrombosis and Haemostasis, 1993)
The effect of nitrogen-(N2-)microbubbles on platelets resembles that of common platelet agonists with respect to aggregation and secretion, but is considerably slower and is poorly inhibited by aspirin. This paper reports the effect of microbubbles on platelet phospholipase C activity in gelfiltered human platelets prelabelled with [32P]Pi ([32P]-GFP). The experiments were run in the presence of an ADP scavenging system in order to rule out effects of ADP. Stimulation of [32P]-GFP for 30 min with microbubbles caused a significant reduction in single platelets (p <0.0004) and a significant increase in 32P-activity in the phosphatidic acid (PA) fraction (p <0.02). Epinephrine potentiated the microbubble-induced reduction in single platelets (p <0.05), but did not enhance the amount of 32P in the platelet [32P]PA fraction. The 32P-radioactivity in the PI-fraction increased with time to a similar extent when [32P]-GFP was stirred for 30 min in absence of microbubbles as it did after 30 min of agonist exposure. There were no significant changes in the [32P]PIP and [32P]PIP2 fractions. Aspirin abolished the microbubble-induced increase in 32P-activity in the PA fraction, but had no significant effect on the reduction in single platelets. Aspirin had a small but significant, reducing effect on platelet aggregation induced by a combination of epinephrine and microbubbles (p <0.05). With epinephrine, however, aspirin did not completely abolish the increase in [32P]-PA. It is concluded that microbubbles alone cause platelets to aggregate by a novel mechanism that operates independent of cyclooxygenase-dependent arachidonic acid metabolites and phospholipase C activation.